Surveys of Afrotemperate forests yields two new freshwater crabs (Decapoda: Potamonautidae: Potamonautes MacLeay, 1838) from South Africa - Daniels, Savel R; Barnes, Aaron; Marais, Hannes; Gouws, Gavin (European Journal of Taxonomy, 2021)
Sampling of remote inland aquatic habitats in South Africa has constantly been yielding novel endemic freshwater crab species (Potamonautes MacLeay,1838). During the present study, we report on the discovery and description of two new freshwater crab species (Potamonautes baziya sp. nov., and P. mariepskoppie sp. nov.) from Afrotemperate forested mountain regions in the Eastern Cape and Mpumalanga provinces of South Africa, respectively. Phylogenetic evidence derived from DNA sequence data of three partial mitochondrial loci (12S rRNA, 16S rRNA and cytochrome oxidase subunit one, COI) corroborates the evolutionary distinction of the two novel species. In addition, morphological and ecological data for the two new species further delineate their evolutionary distinction from congeneric sister species. A comparison of the taxonomically important gonopods 1 and 2 and carapace features among the sister species and other known freshwater crabs of South Africa was further used to provide evidence for the distinction of the two novel species. The discovery of two new species suggest that remote mountainous areas or unsampled regions in South Africa likely harbor several novel species, reiterating a call to document aquatic inland biodiversity in forested and mountainous regions of the country.